UPAYA PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN DALAM PENANGGULANGAN TINDAK PIDANA PENCUCIAN UANG - Eko Raharjo (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
The issue of crime not only from the public spotlight in the local and national level, but also a serious concern of the international community. One crime that is now often used as a discussion by scholars of law, economics and banking apparatus of government and law enforcement are on the money laundering crime (money laundering), especially with the notion that the Republic of Indonesia is "heaven" for these practices criminal offenses or the crime of money laundering. The legal issues increasingly into the spotlight with the inclusion of the Republic of Indonesia in the black list or black list. Keywords: Center for Financial Transaction Reporting and Analysis, Money Laundering